Exposing hidden endemism in a Neotropical forest raptor using citizen science. (20th September 2014) - Lees, Alexander C.; Martin, Robert W.; Amar, Arjun
<x xml:space="preserve">Abstract</x> Gaps in our knowledge of the geographical distribution of species represent a fundamental challenge to biogeographers and conservation biologists alike, and are particularly pervasive in the tropics. Here we highlight the case of the Rufous‐thighed Kite Harpagus diodon, a South American raptor commonly mapped as resident across half the continent. Recent observations at migration watch points have indicated it may be partially migratory in the southernmost parts of its range. To investigate this possibility, we collated contemporary and historical specimen records, published sight records and 'digital vouchers' – photographs and sound‐recordings archived online (from citizen science initiatives) – and explored the spatiotemporal distribution of records. We were unable to trace any documented records of this species from Amazonia during the austral summer (October–March), or records from the Atlantic Forest biome during the peak of the Austral winter (June–August), and all proven breeding records stem from the Atlantic Forest region. We compared this pattern with that of a 'control' species, the congeneric Double‐toothed Kite H. bidentatus, again using specimens and digital vouchers. For this species we found no evidence of seasonality between biomes and can disregard spatiotemporal variation in observer effort as a cause of seasonal biases. We consider that all populations of Rufous‐thighed Kites are fully migratory, wintering in Equatorial forests in the Amazonian basin. We provide evidence that this pattern was previously obscured by erroneous undocumented records and poor or erroneous specimen metadata, and its discovery was primarily facilitated by digital vouchers. This discovery requires a reassessment of the species' global conservation status as an Atlantic Forest breeding endemic, threatened by habitat loss and degradation, as it was previously considered to be resident across large swathes of undisturbed Amazonian Forest on the Guiana Shield. The bulk of the digital voucher data used to elucidate this pattern were extracted from a Brazilian citizen science initiative WikiAves, which may serve as a model for collating biodiversity data in megadiverse countries and help catalyse environmental awareness.